Long‐term outcome in children with juvenile dermatomyositis: A single‐center study from north India. (3rd December 2019) - Sharma, Avinash; Gupta, Anju; Rawat, Amit; Suri, Deepti; Singh, Surjit
Abstract: Introduction: Juvenile dermatomyositis (JDM) is the commonest childhood inflammatory myopathy. Outcome of children with JDM has improved significantly with current treatment protocols. We undertook this study to evaluate long‐term outcome of these children using validated outcome measures. Methods: All children diagnosed as JDM and on follow‐up for more than 2 years were eligible for enrolment. Cross‐sectional examination was performed to assess signs of disease activity, damage, physical function and complications by using multiple validated outcome measures/tools. Results: Thirty‐seven patients were enrolled, 19 were male. Median duration of disease at time of enrolment was 73 months (range 24‐219 months) and median duration of follow‐up was 60 months (range 24‐218 months). Disease course was monocyclic in two‐thirds of patients. Eight children were still on therapy at the time of enrolment. On Manual Muscle Testing 8, 3 and 7 children had severe weakness and mild to moderate weakness, respectively. Neck flexors were the most commonly affected muscle group. On abbreviated Cutaneous Assessment Tool, 14 children had evidence of cutaneous activity. More than 50% had at least 1 sign of cutaneous damage, most common signs being calcinosis and lipodystrophy. Nearly two‐thirds of patients had damage in at least 1 organ using Myositis Damage Index. Nine children had physical dysfunction when assessed by Child Health Assessment Questionnaire. Conclusions: Skin disease continued to be active in a significant proportion of patients. Features of damage, namely calcinosis and lipodystrophy, were seen in more than half. Muscle disease normalized in a large proportion of patients.